IMPACT OF IRRIGATION OF REPEATED CROPS WITH LOW-MINERALIZED DRINK WATER ON SOIL SALINATION LEVEL - O. M. Yusupova (Modern American Journals, 2025)
This article provides information on the effects of Nanosilicon and AMINOSID Universal Si biopreparations on the soil salt and nutrient content of millet and sunflower crops grown as repeated crops in conditions of alluvial, moderately saline soils in the Bukhara oasis, irrigated with low-mineralized ditch waters.
Keywords: Water level, well water, mineralization, biopreparation, Nanosilicon, AMINOSID Universal, dry residue, chlorine ion.